Historical timber as a sustainable material, Studies about Islamic architecture in Egypt - Said, Dalia Shebl (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2018)
Wood is an old â€“ modern material, It was and still used in a wide range in a various purposes as construction, decoration and remains the most popular material all over the world, The research provides an overview of the role ofÂ timber as an important heritage element which forms the main characters and distinguishes features of many historical buildings in Islamic architecture and used widely in many applications, it had been played a great role in construction and structure of buildings, besides that it had been used in a beautiful purpose in different places whether indoors or outdoors use . The research presents the case studies of historical timber in different types of building in Islamic architecture which constructed from more than 1400 years ago, although the historical timber in old buildings exposed to many disasters and faced quite numbers of problems as a result of natural phenomena, man-made, humidity, and termites but it still stands proudly as a great sustain materials. The research shows how he use of timber in historical buildings as sources of inspiration and living evidence of ways of sustainable building practices the types of deterioration which appeared clearly an effect on the statue of historical timber, for that the research introduces some recommendations in the light of ICOMOS international charter â€œ Principles for the Preservation of Historic Timber Structures 1999â€ that Emphasizes the necessity of taking a serious steps and clear strategy to save our heritage elements